Combining Sevoflurane Anesthesia with Fentanyl–Midazolam or S-Ketamine in Laboratory Mice - Cesarovic, Nikola (American Association for Laboratory Animal Science, 2012)
Laboratory mice typically are anesthetized by either inhalation of volatile anesthetics or injection of drugs. Here we compared the acute and postanesthetic effects of combining both methods with standard inhalant monoanesthesia using sevoflurane in mice. After injection of fentanyl–midazolam or S-ketamine as premedication, a standard 50-min anesthesia was conducted by using sevoflurane. Addition of fentanyl–midazolam (0.04 mg/kg–4 mg/kg) induced sedation, attenuation of aversive behaviors at induction, shortening of the induction phase, and reduced the sevoflurane concentration required by one third (3.3% compared with 5%), compared with S-ketamine (30 mg/kg) premedication or sevoflurane alone. During anesthesia, heart rate and core body temperature were depressed significantly by both premedications but in general remained within normal ranges. In contrast, with or without premedication, substantial respiratory depression was evident, with a marked decline in respiratory rate accompanied by hypoxia, hypercapnia, and acidosis. Arrhythmia, apnea, and occasionally death occurred under S-ketamine–sevoflurane. Postanesthetic telemetric measurements showed unchanged locomotor activity but elevated heart rate and core body temperature at 12 h; these changes were most prominent during sevoflurane monoanesthesia and least pronounced or absent during fentanyl–midazolam–sevoflurane. In conclusion, combining injectable and inhalant anesthetics in mice can be advantageous compared with inhalation monoanesthesia at induction and postanesthetically. However, adverse physiologic side effects during anesthesia can be exacerbated by premedications, requiring careful selection of drugs and dosages.